1991
DOI: 10.1210/endo-129-4-2058
|View full text |Cite
|
Sign up to set email alerts
|

Functional Properties of Two Naturally Occurring Isoforms of the Human Insulin Receptor in Chinese Hamster Ovary Cells*

Abstract: We and others have previously demonstrated that the human insulin receptor messenger RNA (mRNA) is alternatively spliced such that the 36-nucleotide sequence encoded by exon 11 of the receptor gene is included (Ex11+) or excluded (Ex11-). Although both Ex11- and Ex11+ insulin receptors which differ in the presence or absence of 12 amino acids in the carboxy-terminal alpha-subunit have been demonstrated to function as insulin receptors when independently overexpressed and studied, the possibility that subtle fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
92
1
2

Year Published

1995
1995
2015
2015

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(103 citation statements)
references
References 40 publications
8
92
1
2
Order By: Relevance
“…IR-A shows a higher affinity for insulin and a higher internalization rate than IR-B (Vogt et al 1991, Yamaguchi et al 1991, whereas IR-B is considered to transmit the insulin signal more efficiently than IR-A as long as it has a greater kinase activity (Kellerer et al 1992, Kosaki et al 1995. Besides, recent studies have shown that IR-A and IR-B activate different downstream pathways.…”
Section: Introductionmentioning
confidence: 99%
“…IR-A shows a higher affinity for insulin and a higher internalization rate than IR-B (Vogt et al 1991, Yamaguchi et al 1991, whereas IR-B is considered to transmit the insulin signal more efficiently than IR-A as long as it has a greater kinase activity (Kellerer et al 1992, Kosaki et al 1995. Besides, recent studies have shown that IR-A and IR-B activate different downstream pathways.…”
Section: Introductionmentioning
confidence: 99%
“…These isoforms have small dierences in binding insulin and mediating the insulin signal (Yamaguchi et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…This insertion is encoded by the 36 nucleotide exon 11 of the receptor gene . The A and B isoforms have different tissue distributions (Moller et al 1989 and functional properties (Yamaguchi et al 1991, Kosaki et al 1995. The a subunit in the rab IR was found to be highly homologous with the a subunits of human IR isoform A without insertion of exon 11.…”
Section: Discussionmentioning
confidence: 99%